2022
DOI: 10.1177/01632787221098119
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Workplace Bullying Among Healthcare Professionals in Tertiary Care Hospitals in Pakistan

Abstract: Workplace bullying (WPB) in the healthcare system (HCS), whether perpetrated by healthcare professionals (HCPs) or patients, is a serious problem. The goal of this research study was to find out how common WPB is among HCPs. We conducted a questionnaire-based cross-sectional study in the three public tertiary care hospitals of Karachi, Pakistan from May to October 2020. A validated Negative Acts Questionnaire-Revised (NAQ-R) was used to measure WPB prevalence. The final sample size was 449, out of which 72.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Many incidents of workplace bullying are reported in the healthcare sector, about 20% rise in workplace bullying is observed in USA hospitals during last few years [ 6 ]. A recent study conducted in the hospital of Karachi have shown prevalence of workplace bullying in health care sector and results have shown that 53% males and 38% of females are victims of bullying [ 7 ]. These figures shows that the situation is becoming alarming therefore there is an urgent need to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Many incidents of workplace bullying are reported in the healthcare sector, about 20% rise in workplace bullying is observed in USA hospitals during last few years [ 6 ]. A recent study conducted in the hospital of Karachi have shown prevalence of workplace bullying in health care sector and results have shown that 53% males and 38% of females are victims of bullying [ 7 ]. These figures shows that the situation is becoming alarming therefore there is an urgent need to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…O NAQ-R tem sido amplamente utilizado em pesquisas internacionais para avaliar o bullying entre trabalhadores, especialmente profissionais da saúde, que são reconhecidos como alvo de bullying em vários países 12,18,19 . No Brasil, há uma lacuna de estudos com o uso de medidas específicas para avaliação do bullying em profissionais de enfermagem.…”
Section: Introductionunclassified